2007
DOI: 10.1159/000104098
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Intensity Combined Training on Women over 65

Abstract: Background: Many studies have sought to assess the effects of physical exercise on older people, but there is little scientific evidence concerning its effects on subjects’ quality of life and cognitive function. Besides, there is a need to know how well the elderly can tolerate combined exercise programs of great intensity and frequency, without risking their health. Objectives: To determine whether older people are able to do a high-intensity combined program of physical exercise, and to analyze its effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
56
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 46 publications
8
56
0
2
Order By: Relevance
“…Moreover, the RCT of Ruoti et al [17] revealed improvements between and within groups in VO 2 max and heart rate (HR), while Taunton et al [19] highlighted a 11.7% of improvements in VO 2 max of the water-based exercise group, but the improvement was statistically significant only in the within group analysis. Finally, only the RUT of Cancela Carral et al [18] did not find any statistically significant change in VO 2 max and in the 2,000-m walk time. From the available literature and the criteria set in this review, it appears that the utilization of water exercise as a method to improve aerobic (cardiovascular) capacity in healthy elderly is supported by strong evidence.…”
Section: Aerobic Capacitymentioning
confidence: 72%
See 1 more Smart Citation
“…Moreover, the RCT of Ruoti et al [17] revealed improvements between and within groups in VO 2 max and heart rate (HR), while Taunton et al [19] highlighted a 11.7% of improvements in VO 2 max of the water-based exercise group, but the improvement was statistically significant only in the within group analysis. Finally, only the RUT of Cancela Carral et al [18] did not find any statistically significant change in VO 2 max and in the 2,000-m walk time. From the available literature and the criteria set in this review, it appears that the utilization of water exercise as a method to improve aerobic (cardiovascular) capacity in healthy elderly is supported by strong evidence.…”
Section: Aerobic Capacitymentioning
confidence: 72%
“…One additional study [11] was excluded because muscle strength of the expiratory and inspiratory muscles was not consider as an index of aerobic or endurance capacity. Among the included studies, five were RCTs [12][13][14][15][16], three studies were randomized UTs [17][18][19] and one study was a CT [20].…”
Section: Search Resultsmentioning
confidence: 99%
“…Although studies have reported conflicting findings on the role of resistance-exercise training in preventing cognitive decline with age, many studies have demonstrated a beneficial effect of such training on specific cognitive measures. In comparing resistance-exercise training with other types of exercise training such as flexibility, tone, relaxation, calisthenics, and even endurance exercises (Brown et al, 2009;Cancela Carral & Ayan Perez, 2007;Ozkaya et al, 2005), some studies have shown that resistance training produces equivalent or increased specific cognitive performances. These beneficial effects were supported by both behavioral and neuroelectric cognitive functions (Ozkaya et al, 2005).…”
Section: General Discussion and Future Directionmentioning
confidence: 99%
“…Ten studies that examined the effects of resistance training on different aspects of cognition were identified: Three studies examined resistance exercise versus nonexercise (Kimura et al, 2010;Liu-Ambrose et al, 2008;Perrig-Chiello, Perrig, Ehrsam, Staehelin, & Krings, 1998; see Table 1), four studies compared multiple exercise modalities (Brown, Liu-Ambrose, Tate, & Lord, 2009;Cancela Carral & Ayan Perez, 2007;Komulainen et al, 2010;Ozkaya et al, 2005;see Table 2), and three studies examined dose-response relationships (Cassilhas et al, 2007;Liu-Ambrose et al, 2010;Tsutsumi, Don, Zaichkowsky, & Delizonna, 1997; see Table 3). Perrig-Chiello et al (1998) evaluated the effects of an 8-week resistance-training program on performance involving multiple cognitive tasks.…”
Section: Reviews Of the Literature Related To Resistance Exercise Andmentioning
confidence: 99%
See 1 more Smart Citation